Influence of Temperature on Energetic and Rheological Characteristics of PLANTOHYD Bio Lubricants – a Study in the Laboratory - Kardjilova, K.; Vozarova, V.; Valah, M. (Engineering, Technology & Applied Science Research, 2013)
This article presents the results of measuring the calorific value and the rheological characteristics of Plantohyd bio lubricants. Measurements were conducted under laboratory conditions with an IKA C5000 calorimeter and a DV-3P Anton Paar digital viscometer. Results are presented graphically. It is shown that the physical interpretation of energy values results ​​and the dependence of rheological properties on temperature can be used to assess the quality of lubricants.